INTRODUCTION OF SHOPEE E-COMMERCE AND SIMPLE BOOKKEEPING IN INCREASING SALES OF MSME PRODUCTS IN KAMPUNG BARU VILLAGE, PAMARAYAN DISTRICT, SERANG REGENCY: PENGENALAN E- COMMERCE SHOPEE DAN PEMBUKUAN SEDERHANA DALAM PENINGKATAN PENJUALAN PRODUK UMKM DI DESA KAMPUNG BARU KECAMATAN PAMARAYAN KABUPATEN SERANG - Raden Irna Afriani; Novi Handayani; Andika Deva Yani; Agung Ramadhan; Nur Sri Udayani; Elsi Afriani; Rizki Badrussalam; Aldi Fatwa Ali; Fadilla Aprilia Ningsi (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Handicraft from bamboo is a beautiful that can make people in the village of Kp Baru, Pamarayan District, Serang Regency, depend on this object for their lives. The results obtained are quite good considering that handicrafts in this village have dominated sales in the Banten Province. However, the craftsmen can not yet develop their sales intensively and also have not been able to prepare financial accounting reports by utilizing the sophistication of information technology. For this reason, this activity is carried out by a service team to increase sales and the welfare of the craftsmen and village communities. It is hoped that after this counseling is carried out, the product from Kp Baru can be owned by all Indonesian people